Good or bad, ups and downs, and getting better: Use of personal health data for temporal reflection in chronic illness. (October 2016) - Barbarin, Andrea M.; Klasnja, Predrag; Veinot, Tiffany C.
Highlights: 38 families with HIV+ or type 2 diabetes patients were studied over 2 years. Patients/families' temporal information needs are met by clinical and non-clinical sources. Needs include status, trends, timing, frequency, cause/effect, and expectations. Patients/families have difficulty seeing causal relationships and trends over time. Abstract: Background: Time is a central component of the experience of illness. Yet, little is known about how chronically ill patients and their family members use temporal information (i.e., information that is dependent on some measurement of time) to reflect upon the illness experience. Objectives: The purpose of this study is to explore what temporal information chronically ill patients and their family members need, where they obtain it, and how they use it, along with related temporal reasoning processes and challenges. Methods: A series of five qualitative, semi-structured interviews were conducted during a two-year longitudinal study of 38 families (97 individuals) with at least one chronically ill member (HIV/AIDS or type 2 diabetes). Results: Patients and family members had temporal information needs related to identifying: patient status; trends; optimal timing, optimal frequency, cause and effect; and what to expect. They used a wide range of information sources to meet these needs, including clinical test results, at-home health monitoring technologies, patient physical appearance and physical sensations, and information about other patients' experiences. Participants employed several forms of reasoning to reflect on temporal information: criteria reasoning (i.e., comparison to a standard), comparative reasoning (both to oneself in the past and to other people), cause-to-effects, effects-to-cause reasoning, conditional reasoning (i.e., if-then reasoning), and deductive reasoning. They used temporal information to carry out instrumental illness management, and to meet emotional and social needs. Patients and families confronted challenges in selecting relevant data, recognizing patterns in those data, and in drawing conclusions based on inferred patterns. Conclusions: Patients have six main temporal information needs, and they use a variety of information sources and reasoning strategies to meet these needs. They also confront important challenges in using temporal information. Based on our results, we offer design principles for systems that support patient and family member temporal reflection. We recommend that such technologies: (1) minimize user burden; (2) leverage existing dissemination channels; (3) include both clinical and non-clinical information; (4) meet informational, emotional and social needs; and (5) facilitate collaborative sense-making among patients and family.